2016
DOI: 10.1128/aem.01173-16
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia ruckeri Isolates Recovered from Diseased Atlantic Salmon (Salmo salar) in Scotland Are More Diverse than Those from Rainbow Trout (Oncorhynchus mykiss) and Represent Distinct Subpopulations

Abstract: Yersinia ruckeri is the etiological agent of enteric redmouth (ERM) disease of farmed salmonids. Enteric redmouth disease is traditionally associated with rainbow trout (Oncorhynchus mykiss, Walbaum), but its incidence in Atlantic salmon (Salmo salar) is increasing. Yersinia ruckeri isolates recovered from diseased Atlantic salmon have been poorly characterized, and very little is known about the relationship of the isolates associated with these two species. Phenotypic approaches were used to characterize 109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…This issue can be resolved by including new isolates in the improved vaccine preparation, as shown with AquaVac(®) RELERA™ that contains both biotypes 1 and 2 of Y. ruckeri and provides better protection [8][9]. Moreover, distinct strains of Y. ruckeri are present in the environment and can evolve with the introduction of susceptible hosts and vaccination of salmonids in aquaculture [10][11]. As the production of global aquaculture continues to increase it is likely that vaccines against other bacterial disease will encounter similar issues and will need the development of improved formulations.…”
Section: Introductionmentioning
confidence: 99%
“…This issue can be resolved by including new isolates in the improved vaccine preparation, as shown with AquaVac(®) RELERA™ that contains both biotypes 1 and 2 of Y. ruckeri and provides better protection [8][9]. Moreover, distinct strains of Y. ruckeri are present in the environment and can evolve with the introduction of susceptible hosts and vaccination of salmonids in aquaculture [10][11]. As the production of global aquaculture continues to increase it is likely that vaccines against other bacterial disease will encounter similar issues and will need the development of improved formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Yersinia ruckeri ( Y. ruckeri ) is a Gram-negative rod-shaped enterobacterium and the causative agent of enteric red mouth disease (ERM), one of the most serious septicemic bacterial disease of salmonid fish species ( 1 ). It has been reported that Y. ruckeri has been increasingly widespread and been detected as an important pathogen of salmonid fish in many other countries ( 2 – 6 ) since its isolation in North American ( 7 10 ). Apart from salmonids, Y. ruckeri can also infect other non-salmonid fish species including common carp ( 11 ), whitefish ( 12 ), sturgeon ( 13 – 15 ), and channel catfish ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enteric redmouth (ERM) disease caused by the enterobacterium Yersinia ruckeri is a contagious disease in finfish with cultured salmonid species, including rainbow trout (Oncorhynchus mykiss), being especially susceptible. Among the identified six different serotypes (O1, O2, O3, O5, O7 and O8) of Y. ruckeri, motile strains belonging to serotype O1 (biotype 1) are considered as the most virulent and has been reported as the cause of outbreaks of ERM in cultured salmonids (Barnes, 2011;Furones, Rodgers, & Munn, 1993;Ormsby et al, 2016;Romalde & Toranzo, 1993;Welch et al, 2011). Subsequently, highly virulent non-motile strains of Y. ruckeri serotype O1 (biotype 2) have emerged in Europe (Davies & Frerichs, 1989) and spread worldwide in reoccurring ERM outbreaks in salmonid aquaculture (Arias et al, 2007;Bastardo, Sierralta, Leon, Ravelo, & Romalde, 2011;Huang et al, 2013;McArdle, 2014;Str€ om-Bestor et al, 2010;Wheeler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%